First realization of the piezoelectronic stress-based transduction device. (25th August 2015) - Chang, Josephine B; Miyazoe, Hiroyuki; Copel, Matthew; Solomon, Paul M; Liu, Xiao-Hu; Shaw, Thomas M; Schrott, Alejandro G; Gignac, Lynne M; Martyna, Glenn J; Newns, Dennis M
Abstract: We present the first realization of a monolithically integrated piezoelectronic transistor (PET), a new transduction-based computer switch which could potentially operate conventional computer logic at 1/50 the power requirements of current Si-based transistors (Chen 2014 Proc. IEEE ICICDT pp1–4 ; Mamaluy et al 2014 Proc. IWCE pp1–2 ). In PET operation, an input gate voltage expands a piezoelectric element (PE), transducing the input into a pressure pulse which compresses a piezoresistive element (PR). The PR resistance goes down, transducing the signal back to voltage and turning the switch 'on'. This transduction physics, in principle, allows fast, low-voltage operation. In this work, we address the processing challenges of integrating chemically incompatible PR and PE materials together within a surrounding cage against which the PR can be compressed. This proof-of-concept demonstration of a fully integrated, stand-alone PET device is a key step in the development path toward a fast, low-power very large scale integration technology.